The Role of Sphingolipid Metabolism in Bone Remodeling - Tang Qi (Frontiers Media S.A., 2021)
Emerging studies of bioactive lipids have made many exciting discoveries in recent years. Sphingolipids and their metabolites perform a wide variety of cellular functions beyond energy metabolism. Emerging evidence based on genetically manipulated mouse models and molecular biology allows us to obtain new insights into the role sphingolipid played on skeletal remodeling. This review summarizes studies or understandings of the crosstalk between sphingomyelin, ceramide, and sphingosine-1-phosphate (S1P) of sphingolipids family and the cells, especially osteoblasts and osteoclasts of the bone through which bone is remodeled during life constantly. This review also shows agonists and antagonists of S1P as possible therapeutic options and opportunities on bone diseases.